Difficulties of Ibaloy learners of English simple primary conjunctions - Anis, Basilio 1929- ([Quezon City s.n.], 1971)
The difficulties of Ibaloy learners in the use of English simple primary conjuctions were predicted in this study. The descriptive-contrastive analysis of English and Ibaloy simple primary conjunctions presents the types of relationships of simple primary conjunctions with other word groups and subject predicate word groups.
Thesis (M. Ed.)--University of the Philippines.
Keywords: English language -- Study and teaching -- Ibaloy students; English language -- Conjunctions